Generous Philanthropy Lazismu as a Form of Social Solidarity for Muhammadiyah Citizens in Sorong Regency - Irianti, Mustika; Al Jumroh, Siti Fatihaturrahmah (Postgraduate Program Magister Pendidikan Agama Islam, 2022)
The purpose of this study is to evaluate the Muhammadiyah people's altruism and generosity during the Covid-19 pandemic in the Sorong district using Lazismu. In this case, one of the Muhammadiyah Amil Zakat and Alms Institutions, often referred to as Lazismu, has been instrumental in raising locals' knowledge of the need of dispersing aid from zakat and alms. Despite Lazismu's zeal for carrying out its operations, there are still many Muhammadiyah members' support mechanisms for other Muhammadiyah members that need to be scrutinized, since they haven't entirely made room for Lazismu to function effectively. This study's implementation took place at Lazismu, Sorong Regency. Sources of data were obtained from Muhammadiyah members who contributed to Lazismu. The method used is the qualitative method. Researchers see the existing phenomena related to the generosity of Muhammadiyah residents through Lazismu. Based on the results of research and data analysis conducted, it can be concluded that the level of generosity through Lazismu is very high.